1988
DOI: 10.1083/jcb.106.5.1507
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Plasmodium falciparum rhoptry protein into the plasma membrane of host erythrocytes.

Abstract: Abstract. The rhoptry is an organelle of the malarial merozoite which has been suggested to play a role in parasite invasion of its host cell, the erythrocyte. A monoclonal antibody selected for reactivity with this organelle identifies a parasite synthesized protein Of 110 kD. From biosynthetic labeling experiments it was demonstrated that the protein is synthesized midway through the erythrocytic cycle (the trophozoite stage) but immunofluorescence indicates the protein is not localized in the organelle unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 31 publications
4
84
0
Order By: Relevance
“…Leaked RhopH complex, and therefore parasite-infected erythrocytes, are then potential targets of host immunity. Indeed, the PfRhopH complex and rhoptry-associated protein 2 (RAP-2, RSP-2), another malaria rhoptry protein, have been detected on the erythrocyte surface upon parasite attachment to erythrocytes [41,42]. The last possibility is that RhopH1/Clag, after release into the PV, may be distributed to the parasite-derived membranous network (i.e., Maurer's clefts) in the erythrocyte cytosol, where it is exposed to host immunity.…”
Section: Diversifying Selection On the Rhoph1/clag Gene Locimentioning
confidence: 99%
“…Leaked RhopH complex, and therefore parasite-infected erythrocytes, are then potential targets of host immunity. Indeed, the PfRhopH complex and rhoptry-associated protein 2 (RAP-2, RSP-2), another malaria rhoptry protein, have been detected on the erythrocyte surface upon parasite attachment to erythrocytes [41,42]. The last possibility is that RhopH1/Clag, after release into the PV, may be distributed to the parasite-derived membranous network (i.e., Maurer's clefts) in the erythrocyte cytosol, where it is exposed to host immunity.…”
Section: Diversifying Selection On the Rhoph1/clag Gene Locimentioning
confidence: 99%
“…The observation that attached, but not internalized, parasites were labeled also suggests removal of surface components of the para- have shown that malaria merozoites labeled with fluorescent fatty acids transfer fluorescent material to the parasitophorous vacuole during invasion (41). Specific proteins (42,43) and lipids (41) are thought to be transferred from the apical organelles during invagination, contributing to the formation of the PVM. Taken together, the available data suggest that, after the initial contact of T. gondii tachyzoites with the surface of the host cell, interchange of surface components of the two interacting cells takes place.…”
Section: Formation Of the Parasitophorous Vacuolementioning
confidence: 99%
“…Release from the erythrocyte triggers the movement of AMA1 to the cell surface where it functions in invasion (7,8). Similarly, rhoptries sequester a different set of proteins and their contents are released onto the erythrocyte surface (4,9), presumably to break the local cytoskeleton and to initiate formation of the parasitophorous vacuole. Taken together, these observations provide evidence for compartmentalization of parasite proteins into distinct organelles with related functions in invasion.…”
mentioning
confidence: 99%